Modificação da superfície do aço AISI 4140 pela nitretação por plasma - Monção, Francisco das Chagas (2019)
Currently, the plasma nitriding process is presented as an excellent alternative for thermochemical treatment to meet the growing demand of industries of various segments for surface treatments in machine parts, made of low alloy steels that promote the hardening of surfaces of these parts with significant improvements in their wear resistance, preserving the core tenacity of the material and ensuring a good life performance in fatigue. Compared to most treatments available on the market, plasma nitriding provides hardening of the surface of low alloy steels in a short time, ensuring the above mentioned properties without undesirable phase change effects of the material structure during the treatment. In this context, the present work aims to study and present the results for practical applications of plasma nitriding of AISI 4140 steel that is widely used in several industrial segments. The samples were submitted to plasma nitriding with gas mixture in the proportion of 25% vol.N2: 75% vol.H2 for 3 hours and at three temperature ranges: 500 ° C, 550 ° C and 600 ° C. After the treatment, characterization tests were performed by optical microscopy, scanning electron microscopy and X- ray diffraction with the aim of verifying the microstructure, the morphology, the thickness of the nitrided layer named as compound layer also known as “white layer" and the phases. Were also carried out tests with atomic force microscopy to verify the topography of the nitrided surface as well as the morphology of the nitride layers. The results show an increase in the surface roughness of the samples, caused by the sputtering process in argon and nitrogen plasma. Measurements of surface microhardness after nitriding showed values between 649 and 759HV0.05, significantly higher than those obtained before treatment between 280 and 300HV1. Finally, the microhardness profile was measured to determine the total depth of the nitrided layers. As a result, a depth varying between 256 and 358μm was obtained, according to the nitriding temperature level.